Delayed aortic regurgitation after TEVAR procedure: a case report - Soo Jin Park; Seungwook Lee; Jeong A Son; Seungji Hyun; Do Jung Kim; Sang Hyun Lim; You Sun Hong (Journal of Cardiothoracic Surgery, 2022)
Abstract Background Acute aortic regurgitation (AR) is uncommon condition and usually results in an emergent situation because the left ventricle does not adapt quickly due to a sudden increase in end-diastolic volume caused by the regurgitant flow. Thoracic endovascular aortic repair (TEVAR) is a procedure that places a stent-graft on the lesion of thoracic aorta through a minimally invasive approach. Case presentation Here we report that a catheter-induced aortic valve injury associated with TEVAR can cause delayed AR, exemplified by the case of a patient who developed acute AR 42 months after TEVAR. For this, aortic valve replacement was performed and the patient was discharged without complications. Conclusion Our results demonstrate that when a catheter-related procedure is performed around the aortic valve, slight injury of the valve can cause aortic insufficiency even 3 years after surgery. Consequently, when performing a catheter-related procedure around the aortic valve, special attention is always required.